2012
DOI: 10.1073/pnas.1215462109
|View full text |Cite
|
Sign up to set email alerts
|

Force measurements on cargoes in living cells reveal collective dynamics of microtubule motors

Abstract: Many cellular cargoes move bidirectionally along microtubules, driven by teams of plus-and minus-end-directed motor proteins. To probe the forces exerted on cargoes during intracellular transport, we examined latex beads phagocytosed into living mammalian macrophages. These latex bead compartments (LBCs) are encased in membrane and transported along the cytoskeleton by a complement of endogenous kinesin-1, kinesin-2, and dynein motors. The size and refractive index of LBCs makes them well-suited for manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
219
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(260 citation statements)
references
References 46 publications
23
219
1
2
Order By: Relevance
“…While this paper was in submission, a similar paper using a similar technique was published (31). The other paper's technique involves measuring the passive and forced response of a trapped cargo in vivo, over many frequencies, and then applying a global fit over the frequencies measured.…”
Section: Methodsmentioning
confidence: 99%
“…While this paper was in submission, a similar paper using a similar technique was published (31). The other paper's technique involves measuring the passive and forced response of a trapped cargo in vivo, over many frequencies, and then applying a global fit over the frequencies measured.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, our current result provides a strong support for the idea that besides its binding to other subunits, the tail is important for regulating dynein motor function in vivo. It is worth pointing out that in vivo, the dynein motor carrying a cargo not only needs to move in a cytoplasm with considerable viscosity (63,64) but also needs to compete with plus-end-directed motors bound to the same cargo (65)(66)(67). In filamentous fungi, kinesin-3 is able to bind to the dynein-bound early endosome and be carried to the minus end as a cargo of dynein (40,53,68).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, Myo1b is termed a 'tension-sensitive tether' because when experiencing no mechanical force, the motor detaches from actin filaments within a second after binding to actin and undergoing its powerstroke; however, under resistive loads as low as 1 pN, Myo1b remains anchored to actin filaments for nearly 100 s. These low forces are well within the range of those expected to take place during intracellular transport and mechanotransduction (Gillespie and Cyr, 2004;Hendricks et al, 2012;Soppina et al, 2009). Recent structural and biophysical studies have shown that the tension sensitivity of Myo1b is due in part to a structural element located within the N-terminus of the motor Shuman et al, 2014).…”
Section: Myosin-i Is a Molecular Dock Or Tethermentioning
confidence: 72%